The Effects of Psychological Contract on Employees Performance in Sarawak Hotel Industry. - Yeo, Chia Swee (2018)
This study investigates the effects of psychological contract on the employees’ performance and the influence of generation affiliation on the relationship between psychological contract and employees’ performance. Specifically, selected social-psychological and human care factors were analyzed. This was accomplished after a concise review of relevant literature which resulted in the development of research objectives and a general conceptual framework with hypotheses to guide the study. Data were collected from a sample of 320 full-time hoteliers in Sarawak’s Five Star Hotels through a survey questionnaire. Structural equation modeling analyses were used to test the impact of the psychological contract on employees’ performance. The impact of the psychological contract on employees’ performance was moderated by generational affiliation. Furthermore, results indicated that different aspects of psychological contract such as employer-employee mutual understanding, perspective relationship, level of interaction, and employees’ perception respond differently toward employees’ performance. The study had presented evidence that different aspects of psychological contract impact on the employees’ performance. The result from this study suggests that there was a significant effect of employers to employee perspective relationship, level of interaction and employees’ perception toward employees’ performance. Results from this study suggest that relationship, communication, group cohesiveness, participation, and involvement improved employees’ performance. Employer-employees’ mutual understanding seem mostly unrelated to employees’ performance. Keywords: psychological contract; generational affiliation; employees’ performance